Estudo transversal sobre saúde mental de agricultores da Serra Gaúcha (Brasil) A cross-sectional study about mental health of farm-workers - Neice MX Faria; Luiz A Facchini; Anaclaudia G Fassa; Elaine Tomasi (Universidade de São Paulo, 1999)
OBJETIVO: Considerando a escassez de estudos rurais de base populacional, buscou-se avaliar as associações entre características do trabalho rural e a ocorrência de morbidade psiquiátrica menor- MPM. MÉTODOS: Utilizando delineamento transversal, estudaram-se 1.282 agricultores de 446 estabelecimentos. As informações foram coletadas por entrevista direta, a partir da percepção do trabalhador. O índice de Kappa foi adotado para controle de qualidade. Caracterizaram-se as condições produtivas, dados sociodemográficos e indicadores de saúde mental. RESULTADOS: A prevalência de MPM afetou 37,5% dos agricultores. As prevalências foram maiores entre produtores de feijão e menores entre os de maçã. Encontrou-se risco aumentado nos estabelecimentos de 26 a 50 ha, e risco reduzido associado à maior mecanização e aumento de escolaridade. A ocorrência de intoxicação por agrotóxicos mostrou forte associação com MPM, embora não se possa definir a direção dessa associação. CONCLUSÕES: Os resultados alertam para a dimensão dos problemas e para a urgência de medidas que visem a proteger a saúde dos agricultores. OBJECTIVE: In view of the shortage of population-based rural studies, this research project evaluated the associations between the characteristics of rural work and the occurrence of minor psychiatric disorders (MPD). METHODS: A cross sectional study was carried out on the 1,282 farm workers of 446 farms. Information about the farms (land extension, agricultural activities, technology and pesticide use) was collected. Demographic and socioeconomic data, characteristics of the work process and mental health indicators were obtained from the workers. RESULTS: MPD were found in 37.5% of the farm workers. The risk was higher on farms with a land extension of from 26 to 50 hectares, and lower where there was an increased level of job technology and schooling. The prevalence of MPD was higher among bean producers and lower among apple producers. Despite the impossibility of defining the direction of the causal link, pesticide poisoning was strongly associated with MPD. CONCLUSION: The results call attention to the dimension of the problem and to the importance of adopting new policies for the protection of farm workers' mental health.